PERUMUSAN NILAI TAMBAH SUATU KAWASAN PARIWISATA: SUATU KERANGKA PEMIKIRAN DARI PENDEKATAN PEMASARAN - Ivantia Savitri Mokoginta (Center for Economic Studies Universitas Katolik Parahyangan, 2000)
This paper proposes the interaction of market, internal and competitor factors in positioning determination of tourism destination. What area of concerned of each factor how these factors interrelated in positioning determination is further explained.